Genetic Polymorphisms rs643627 in Serotonin Receptor Gene (5-HTR2A) with Schizophrenia - Khudhiar, Noor K.; Saud, Asmaa M. (Iraqi Journal of Science, 2019)
Schizophrenia(SCZ) is oneof the most destructive and complicated chronic diseases of the human nervous system. Serotonin receptors have been involved in the pathophysiology of psychiatric disorders including schizophrenia. Fortyschizophrenia subjects (14females and 26 males) with an age range of 23– 57 years were enrolled, in addition to twenty healthy control subjects (10female and 10 male) with an age range of 19-44 years. This study aimed to evaluate the frequency of one single nucleotide polymorphism (SNP), namelyrs643627 in HTR2Agene,inIraqi patients with schizophrenia in comparison with controls, along with the association between this SNP and the incidence of schizophrenia. The genetic variantrs643627 within the intron region of 5-HTR2Agene was genotyped by Real Time –PCR. The results showed that differences in the demographic data of gender and age between schizophrenia subjects and controls were statically non-significant. Also, the genotype frequencies distribution of rs643627 polymorphism showed no deviation from Hardy–Weinbergequilibrium in both groups (patients and controls). In addition,differences in the genotypes(AA, AG, and GG) and allele frequencies of 5-HTR2A were statically non-significant between SCZ patients and controls. However,the present study results demonstrated an association between rs643627 polymorphism of 5-HT2Ageneand age and gender in schizophrenia patients group.